Haemorrhagic complications with adenotonsillectomy in children and young adults with bleeding disorders. (12th January 2015) - Warad, D.; Hussain, F.T.N.; Rao, A.N.; Cofer, S.A.; Rodriguez, V.
Summary Haemorrhagic complications remain a challenge with surgical procedures in patients with bleeding disorders. In children and young adults, the most commonly performed surgeries are tonsillectomies and/or adenoidectomies. Adequate haemostasis in these patients with bleeding disorders is centred on comprehensive perioperative haemostatic support and dexterous surgical technique. The aim of this study was to assess postoperative bleeding complications with tonsillectomy and/or adenoidectomy in children and young adults with known bleeding disorders. Retrospective review of all patients aged <25 years with known bleeding disorders who underwent tonsillectomy and/or adenoidectomy at Mayo Clinic, Rochester MN between July 1992 and July 2012. In contrast to reported literature, we observed a higher rate of bleeding complications (10/19, 53%) despite aggressive haemostatic support and appropriate surgical techniques. Delayed bleeding (>24 h postoperatively) was more common than early bleeding; and recurrent bleeding was associated with older age. Children and young adults with haemorrhagic diatheses undergoing adenotonsillectomy are at a higher risk of delayed bleeding and require close monitoring with haemostatic support for a prolonged duration in the postoperative period. A uniform approach is needed to manage these patients perioperatively by establishing standard practice guidelines and ultimately reduce postsurgical bleeding complications.